Acoustic therapies for tinnitus: The basis and the electroencephalographic evaluation. (May 2020) - Ibarra-Zarate, David; Alonso-Valerdi, Luz María
Abstract: Subjective tinnitus is a complex symptom that has no effective treatment up to now. Several acoustic therapies such as retraining therapy, auditory discrimination therapy, enriched acoustic environment and binaural therapy have been proposed to induce habituation and/or diminution of the tinnitus perception. The effect of the auditory stimulus in use is not, however, well understood yet. At present, the effectiveness of the acoustic therapies on patients suffering from tinnitus is only monitored via visual analog scales or questionnaires, what could not reflect accurately the patient evolution. It is well known that neuroimaging techniques are widely applied to monitor neural activity for diagnosing brain disorders, and predicting treatment outcome success. From those techniques, Electroencephalography (EEG) has become the most commonly used method since it gives an insight into the temporal behavior of neural oscillations, and it is relatively a low-cost and low-maintenance system in comparison to other techniques. EEG signals are modulated by the internal communication between neural networks, and the inter-communication among those networks. As is hypothesized that subjective tinnitus is the result of increased neural synchrony and spontaneous firing rates in the auditory system, EEG analysis may be an objective method to monitor the effect of acoustic therapies for tinnitus. In this paper, the state-of-the-art on acoustic therapies for tinnitus, and recent advances on the follow-up treatment based on EEG analysis is discussed. In general, this paper outlines evidence showing that EEG signal processing offers to investigate (1) internal communication in neural nodes ( absolute and relative power ), (2) inter-communication of neural nodes ( coherence ), (3) time-frequency analysis with high resolution in both low and high frequencies ( Fourier and Wavelet analysis ), (4) rate at which neural information is being produced ( entropy ), (5) genesis of abnormal neural synchrony on the basis of biophysical assumptions ( source localization ) or statistical evaluations ( PCA and ICA ), and (6) level of neural synchrony over time ( ERD/ERS maps ).